2014
DOI: 10.5114/aoms.2014.47827
|View full text |Cite
|
Sign up to set email alerts
|

State of the art paper Tumor necrosis factor inhibitors – state of knowledge

Abstract: Tumor necrosis factor (TNF) is considered a major proinflammatory cytokine, affecting various aspects of the immune reaction. All five TNF inhibitors currently available on the market (i.e., etanercept, infliximab, adalimumab, certolizumab and golimumab) are top sellers, although indicated only in autoimmune diseases, including rheumatoid arthritis, Crohn's disease and psoriasis. This article briefly discusses the background and place for TNF inhibitors in modern therapy. The main safety aspects of TNF inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
149
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(151 citation statements)
references
References 60 publications
(58 reference statements)
2
149
0
Order By: Relevance
“…Infliximab is a human-murine chimeric monoclonal antibody against TNF-α that was approved for the treatment of autoimmune diseases such as Crohn's disease, ulcerative colitis, ankylosing spondylitis and rheumatoid arthritis (Lis et al 2014). It has also been reported that infliximab shows anti-inflammatory and antioxidant effects in a rat model of intestinal ischemia/reperfusion injury (Pergel et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Infliximab is a human-murine chimeric monoclonal antibody against TNF-α that was approved for the treatment of autoimmune diseases such as Crohn's disease, ulcerative colitis, ankylosing spondylitis and rheumatoid arthritis (Lis et al 2014). It has also been reported that infliximab shows anti-inflammatory and antioxidant effects in a rat model of intestinal ischemia/reperfusion injury (Pergel et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence on the comparative effectiveness of one of the most commonly used TNFi, adalimumab, versus the recently approved secukinumab, plays an important role in clinical and healthcare economic decision-making [23]. In the absence of head-to-head trials that compare adalimumab and secukinumab, indirect comparisons can provide valuable information in terms of comparative clinical efficacy and cost-effectiveness [24].…”
Section: Introductionmentioning
confidence: 99%
“…It binds to both soluble and membrane-bound forms of TNF-a, prevents TNF-a from binding to TNFR1 and TNFR2 and can lyse cells with transmembrane TNF-a in vitro and in vivo [43]. Etanercept is a human p75 TNF-receptor Fc (portion of IgG1) dimeric fusion protein administered subcutaneously twice weekly at a 50 mg dose for 3 months, followed by a 50 mg weekly dose thereafter [42,44]. It prevents the binding of TNF-a and TNF-b (also called lymphotoxin a) to cell surface receptors, but it does not lyse cells expressing transmembrane TNF-a [44].…”
Section: Approved Biologic Drugs Targeting Tnf-amentioning
confidence: 99%
“…Adalimumab functions to block the interaction of TNF-a with TNFR1 and TNFR2 and to lyse cells in vitro that express TNF-a in the presence of complement [41]. Infliximab is a chimeric bivalent IgG1k human-murine monoclonal antibody specific for TNF-a, which is administered by intravenous (IV) infusion with a dose of 5 mg/kg at weeks 0, 2 and 6, and every 8 weeks thereafter [42,43]. It binds to both soluble and membrane-bound forms of TNF-a, prevents TNF-a from binding to TNFR1 and TNFR2 and can lyse cells with transmembrane TNF-a in vitro and in vivo [43].…”
Section: Approved Biologic Drugs Targeting Tnf-amentioning
confidence: 99%
See 1 more Smart Citation